Credit cycles and capital flows: Effectiveness of the macroprudential policy framework in emerging market economies - Fendoğlu, Salih (Journal of Banking & Finance, 2017)
I assess the effectiveness of macroprudential policy tools in containing credit cycles per se or the impact of portfolio inflows on the cycles in major emerging market economies. The results show that borrower-based tools, measures with a domestic focus, and domestic reserve requirements are particularly effective. The findings are, in most cases, stronger for the recent period during which most of the macroprudential actions are undertaken, and generally hold for alternative definitions of credit cycle, the monetary policy stance, and portfolio inflows. Weaker results emerge for financial-institutions-based or foreign-currency related macroprudential tools.